DROUGHT COSTS REDUCTION THROUGH RISK MANAGEMENT WITH STAKEHOLDER APPROACH (Costos y Gestión, 2020)
At present there is no market developed in Argentina to transfer systemic risks such as drought and flooding, despite being Agriculture one of the main sources of wealth in the country. Furthermore, these extreme climatic factors are the main cause of losses of the last ten years in this business.The proposal raises three main aspects that we believe to help in its development:The use of technological advances (like the improved Vegetation index - VEI - measured using satellites during the critical crop period). Implementing this index is viable since: ? It reduces the operational costs in the insurance industry. ? It lowers the level of aggregation reducing the base risk. ?  It counts with reliable measurements.The alternative of sharing the risk between the different stakeholders of the Value Chain.The debate and broadcasting of concepts regarding the General Theory of Cost which can clarify the impact of the decrease in business risk on the reduction of the cost of Capital, in order to optimize the added value target.
Keywords: stakeholder theory; risk management; management accounting; TGC; drought